TRANSFORMASI FOURIER, LANGSUNG, RIETVELD: PENENTUAN STRUKTUR KRISTAL OPTIMAL SEBAGAI MATERIAL PERTAHANAN: Fourier Transform, Direct, Rietveld: Determination Of Optimal Crystal Structure As Defense Material - Sianipar, Alexcandro; Talalu, Lidya Ananda; Aritonang, Sovian (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
Determining the optimal crystal structure is essential in the development of defense materials, as its crystal structure influences the physical and mechanical properties of a material. This study employs a mathematical approach to analyze crystal structures through three primary methods: Fourier Transformation, Direct Methods, and the Rietveld method. Fourier Transformation enables the analysis of diffraction data generated by the interaction of X-rays with atoms in a crystal, converting it into electron distribution to identify atomic positions. The Direct Method utilizes probabilistic phase relationships to accurately estimate atomic positions, even when diffraction data is incomplete. The Rietveld method, based on optimization, refines the crystal structure model by comparing experimental diffraction data with simulated results, minimizing differences between them. The analysis results show that the combination of these three methods effectively determines the optimal crystal structure. The implementation of these techniques is expected to support the selection of superior materials for defense applications